“Perspectiva de las relaciones sociales de género y los recursos educomunicativos en Educación” - Altamirano Taipe, Paola Alexandra (2021)
Nowadays it is evident there´s no gender equality in the opportunities for men and women, so it is necessary to understand these existing asymmetries. Thus, the gender perspective looks for deconstruction of stereotypes in the socioeducative context, therefore the school is the space to promote gender social relations, from the transversality in the pedagogical process and the use of educative and communicative resources. In this way, it has been observed the teachers don´t know topics about gender, therefore it hasn´t been included as educative content and the class is an scene where the stereotypes and discriminatory practices have been reproduced. In addition, the lack of knowledge of using educommunicative resources with information about gender equality in order to reflect with the students and promote attitudinal contents. The objective of this study is to develop a methodology about social gender relations through workshops and educommunicative resources for the strengthening of children´s integral training in Catorce de Julio Juan Abel Echeverría school from Latacunga town. The methodology of this project is based on qualitative research and its phases are: preparatory, field, analytical and dissemination. The technique that was applied was observation and the instrument of collecting information was the observation guide, which will obtain information in the educational field for the construction of reflections and propose the methodological guide. The results are reflections and a methodological guide, which has been built with relevant information about gender taken from the media and technological resources. This work contributes to the improvement of social relations from the gender perspective in schools because boys and girls require new forms of socialization, so that stereotypes that denigrate girls from an early age do not continue to be reproduced. Furthermore, it allows for applying educommunicative resources with real information for the development of activities based on critical pedagogics, which contributes to the interpretation of reality and in a particular way guides the analysis of social gender relations among human beings.